Influence of voxel size for µCT imaging of particles on measurement accuracy. (28th June 2021) - Burgmann, Sophie; Godehardt, Michael; Schladitz, Katja; Breit, Wolfgang
Highlights: Influence of µCT voxel size on particle size measurement uncertainty is analysed. A ratio of voxel size to sieve size of 12 is suggested for length measurement. A ratio of voxel size to sieve size of 25 is suggested for volume measurement. Inhomogeneities in particle's mineral composition increase measurement uncertainty. Abstract: Size and shape of particles have a decisive influence on macroscopic properties of building materials. Capturing µCT images (micro-computed tomography) of these particles enables the determination of three-dimensional size and shape parameters. Here, the influence of the structural resolution on the measurement accuracy is studied. µCT images of single particles are taken with varying structural resolution. The experimental results indicate that scanning particles, resolving the particle sieve size with 12 to 25 voxels, yields an acceptable level of measurement accuracy.